2016
DOI: 10.1364/boe.7.002729
|View full text |Cite
|
Sign up to set email alerts
|

Identification of informative bands in the short-wavelength NIR region for non-invasive blood glucose measurement

Abstract: Abstract:The "glucose-linked wavelength" in the short-wavelength nearinfrared (NIR) region, in which the light intensity reflected from the hand palm exhibits a good correlation to the blood glucose value, was investigated. We performed 391 2-h carbohydrate tolerance tests (CTTs) using 34 participants and a glucose-linked wavelength was successfully observed in almost every CTT; however, this wavelength varied between CTTs even for the same person. The large resulting data set revealed the distribution of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Although fairly matured, the analysis of blood glucose by NIR spectroscopy continues to be an intensively studies topic with several recent literature reports reflecting the attention given to this field and the dynamics of the research. Recently, Uwadaira et al re-evaluated in detail the suitability of the absorption bands in LW-NIR (long wavelength) vs. SW-NIR (short wavelength) for blood glucose examination [22,23]. Typically, the LW-NIR region (ca.…”
Section: Glucose In Bloodmentioning
confidence: 99%
See 2 more Smart Citations
“…Although fairly matured, the analysis of blood glucose by NIR spectroscopy continues to be an intensively studies topic with several recent literature reports reflecting the attention given to this field and the dynamics of the research. Recently, Uwadaira et al re-evaluated in detail the suitability of the absorption bands in LW-NIR (long wavelength) vs. SW-NIR (short wavelength) for blood glucose examination [22,23]. Typically, the LW-NIR region (ca.…”
Section: Glucose In Bloodmentioning
confidence: 99%
“…In SW-NIR, however, there appears an absorption gap between visible absorption of hemoglobin and NIR absorption of water, creating an optical window for sensing the deeper layers of the tissue. The studies by Uwadaira et al [22,23] demonstrated that the correlation between SW-NIR spectra and blood glucose content is sufficient to successfully construct calibration models based on partial least squares (PLS) regression. However, this could reliably be done only for individual subjects.…”
Section: Glucose In Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the accuracy of the prediction model can be increased by collecting more NIR spectral data in a controlled environment, research has shown that temperature and light conditions greatly affect the quality of NIR spectral data [12]. The variance in blood glucose data can also be increased to get a better prediction model [13].…”
Section: B Prediction Testingmentioning
confidence: 99%
“…In a previous study, 2 two methods were proposed for realizing a noninvasive blood glucose sensor. One used near-infrared spectroscopy, [3][4][5][6][7][8][9][10] while the other used mid-infrared spectroscopy. [11][12][13] When these methods were applied to measure the blood glucose levels in biological samples, there were two problems.…”
Section: Introductionmentioning
confidence: 99%